Pengaruh Fasilitasi Promosi dan Pemasaran terhadap Kinerja Usaha Mikro, Kecil dan Menengah - Tito Luthfi Novianto Rizaldi; Sartika Djamaluddin (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to investigate the effect of promotion and marketing facilitation on the performance of MSMEs as measured by revenue streams for a year. Promotion and marketing facilitation of MSMEs is carried out through SMESCO, which is a work unit under the Ministry of Cooperatives and SMEs which aims to expand MSME market access both nationally and globally. Promotion and marketing facilitation activities consists of intensive promotion and marketing through offline and online media, implementation of promotional events, marketing partnership cooperation and is supported by increasing the capacity of MSMEs human resources and financing loan facilities. Previous studies have shown that there is a positive and significant influence between promotion, use of online media and partnerships with increasing MSMEs revenue. Through the panel data regression analysis method using the fixed effect estimation model, results can be obtained which state that there is a positive and significant influence between promotion intensity both offline and online, the implementation of promotional events and the implementation of marketing partnership cooperation carried out by SMESCO on the performance of MSMEs as measured by revenue streams. In addition, increasing the capacity of human resources, financing loans and the number of other agencies that also provide guidance to MSMEs as a control variable also has a positive and significant influence on MSMEs revenue. However, the Large-Scale Social Restrictions (PSBB) policy during the COVID-19 pandemic had a negative and significant impact on MSMEs revenue. Keywords: : MSMEs; promotion and marketing facilitation; revenue